If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f(-1x) = 7x + 5 Remove parenthesis around (-1x) f * -1x = 7x + 5 Reorder the terms for easier multiplication: -1f * x = 7x + 5 Multiply f * x -1fx = 7x + 5 Reorder the terms: -1fx = 5 + 7x Solving -1fx = 5 + 7x Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Divide each side by '-1x'. f = -5x-1 + -7 Simplifying f = -5x-1 + -7 Reorder the terms: f = -7 + -5x-1
| 60=2l+2(5w) | | 2(2+3y)-6y=4 | | 5(4+0.5w)+7w=1 | | =-3y^2+2y | | 81=16r^4 | | S+-4=7.3 | | (3x-y)/3 | | 4.2x-86=2.7x+7 | | 4.7x+8.16=2.52 | | 4/9-y/4=7/36 | | h(x)=3x^2-2x | | 8x+7=0*(5x+9) | | d^2-d= | | 8x+7=0*5x+9 | | 6y-15=35 | | (2x+3y)*(4x^2-6xy+9y^2-3)=0 | | 0.75(m−1)−0.5m=5/6(2m−7) | | y-2(1.5+0.5y)=1 | | P=2q+7r | | -2(y+3)+3(3y-7)=6(y-3)+13 | | log[9]7-log[9]10=log[9] | | y^2+8y-16= | | -2(4t-5)+3t=6t-9 | | 0.04*(500+x)=50 | | 7y+3-5y=5+y-5 | | 4x^2-32x=-14 | | 4x^2-32x=-24 | | -8x+10=8-4x-5x | | 3y-5=4y-3 | | 11-2(a-1)=4a+a | | -37+-56= | | 2x/4=7 |